Empowering Parents in Early Childhood Education Through a Participatory Approach in Community Service Activities - Susanti, Siti Misra; Marwah; Hartati; Saleh, Rachman; Hertuni, Firji (TAAWUN, 2025)
This community service aims to empower parents in early childhood education. The importance of early childhood education in shaping children's character, cognitive, social, and emotional development will be more optimal. Early childhood (0-6 years) is the golden age for child development. However, parents' understanding of the importance of PAUD is still minimal, with many assuming that formal education only begins when children enter elementary school. This community service uses lecture and question-and-answer methods between parents, teachers, and community members about early childhood education. to facilitate the active involvement of parents in understanding and implementing early childhood education. Activities carried out in Wakeakea Village, including preparation, implementation of activities, and evaluation. The results of community service provide several solutions, including parental involvement in the education process, collaboration between teachers and parents, namely quality early childhood education involving parents and teachers, in order to create a safe learning environment. Parents as the first educators have a crucial role in providing appropriate stimulation, creating a supportive learning environment, and building responsive parenting patterns, for example, fulfilling financial needs and providing sufficient love and motivation for children to learn in order to create a quality generation.